PENGEMBANGAN BAHAN AJAR BERBASIS PENDEKATAN OPEN ENDED PADA MATERI PENGUKURAN PANJANG DAN BERAT UNTUK MENINGKATKAN KEMAMPUAN PENALARAN SISWA KELAS IV DI SD N BUGANGAN 03 SEMARANG - Happy Prawitasari Nourmaningtyas; Joko Sulianto; Aries Tika Damayani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
The background that encourages this research and development is the lack of teaching materials in the fourth grade mathematics learning at SD NegeriBugangan 03 Semarang. The research objectives to be achieved in this study were to determine the feasibility of developing teaching materials based on an open-ended approach on material measuring length and weight. This research is a research development (Research and Development). The data analysis technique used qualitative descriptive and quantitative descriptive. The feasibility results are based on data analysis by media experts and material experts, and field trial results assessment. The results of the media validation was 90,6%, the material expert validation was 93,3%, and the evaluation of the test results by several teachers for the media was 88,4% and the material was 88%. This shows that teaching materials based on an open-ended approach are suitable for use as supporting teaching materials in mathematics learning. The suggestion that the writer can convey is that hoped that the teacher does not only use one teaching material. At least, teachers use supporting other teaching materials to support the main teaching material. In addition, teachers should pay attention to the level of students reasoning abilities to support students mathematical skills.